Symmetric sodium-ion batteries based on the phosphate material of NASICON-structured Na3Co0.5Mn0.5Ti(PO4)3. Issue 53 (30th June 2017) - Wang, Hongbo; Chen, Chao; Qian, Chao; Liang, Chengdu; Lin, Zhan
Abstract : A NASICON-structured bi-functional phosphate electrode material is developed in symmetric room-temperature sodium-ion batteries (NIBs). Abstract : Symmetric sodium-ion batteries (NIBs) have become a research focus since they employ bi-functional electrode materials as both the cathode and the anode, resulting in reduced manufacturing cost and simplified fabrication process. Layered oxide bi-functional materials have received great attention recently, while phosphate analogues have rarely been involved in the same energy storage system. Herein, we report a new phosphate compound of Na3 Co0.5 Mn0.5 Ti(PO4 )3, and investigate the electrochemical performances of this bi-functional material in traditional organic electrolyte. The results demonstrate that Na3 Co0.5 Mn0.5 Ti(PO4 )3 can deliver compatible capacities of ca. 50 mA h g −1 at a rate of 0.1C in both potential windows of 2.8–4.2 V and 1.6–2.8 V. Furthermore, when applied as anode material for rechargeable NIBs, Na3 Co0.5 Mn0.5 Ti(PO4 )3 can exhibit an impressive cycling stability with capacity retention of 94% exceeding 550 cycles at a rate of 0.2C. In addition, deriving from Na3 Co0.5 Mn0.5 Ti(PO4 )3 as simple active material, we construct a symmetric NIB with an average operation voltage of 1.5 V and a specific energy of about 30 W h kg −1 .